The Effect of The Use of The Digital Qur’an on Incrasin Interest In Reading The Qur’an of Stundent - Nabighah, Mahdiani Zahra; Salim, Hakimuddin (FKIP - Universitas Riau, 2025)
This study sought to ascertain how students in Muhammadiyah University of Surakarta's Islamic Religious Education Study Program might become more interested in reading by using digitized versions of the Qur'an. The growing number of pupils utilizing the digital Qur'an is expected to facilitate access and boost interest in reading. This study uses descriptive and qualitative methodologies to describe how students' interest in reading is affected by using the digital Qur'an. To gather information, students in the Islamic Religious Education Study Program were given a questionnaire to complete. According to the study's findings, the majority of students believe that using a digital Qur'an can make them more interested in reading. Accessibility, the availability of services for translation and interpretation, and audio readings that might enhance comprehension are the primary auxiliary variables. Nevertheless, some students also brought up challenges including the discomfort of reading for extended periods of time on a cellphone screen and the disruption from other apps' notifications. Overall, this study indicated that the digital Qur'an increased students' interest in reading; nevertheless, several aspects still need to be addressed to make this application more focused and pleasant.